Thermoelectric conversion module
The use of a base material with low thermal resistance and high thermal conductivity in thermoelectric conversion modules addresses the limitations of resin substrates, enhancing thermoelectric performance for cooling and power generation applications.
Patent Information
- Application Number
- JP2022510043
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-27
- Filing Date
- 2021-03-18
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2041-03-18
AI Technical Summary
Resin substrates used in thermoelectric conversion modules have low thermal conductivity, leading to insufficient thermal resistance and hindering further improvements in thermoelectric performance.
A thermoelectric conversion module using a base material with thermal resistance of 0.35 K/W or less, composed of a thermoelectric semiconductor material, heat-resistant resin, and an ionic liquid, which enhances thermal conductivity and flexibility.
The module achieves improved thermoelectric performance with increased heat dissipation and flexibility, suitable for applications in cooling and power generation.
Smart Images

Figure 0007621335000002 
Figure 0007621335000003 
Figure 0007621335000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermoelectric conversion module. [Background technology]
[0002] 2. Description of the Related Art Conventionally, one of the effective means for recovering unused waste heat energy generated from fossil fuel resources used in buildings, factories, etc. as a heat source is a thermoelectric conversion module that uses a thermoelectric conversion material having a thermoelectric effect such as the Seebeck effect or the Peltier effect to directly convert thermal energy into electrical energy. As the thermoelectric conversion module, a so-called π-type thermoelectric conversion element is known. The π-type is configured by providing a pair of electrodes spaced apart from each other on a substrate, for example, by providing a P-type thermoelectric element on one electrode and an N-type thermoelectric element on the other electrode, also spaced apart from each other, and connecting the upper surfaces of both thermoelectric materials to the electrodes of the opposing substrate. Also, a so-called in-plane type thermoelectric conversion element is known. The in-plane type is configured by alternately providing P-type thermoelectric elements and N-type thermoelectric elements in the in-plane direction of the substrate, for example, by connecting the lower parts of the junctions between the two thermoelectric elements in series with an electrode interposed therebetween. In recent years, there has been a demand for further improvement in thermoelectric performance, including improvement in flexibility and miniaturization and thinning of thermoelectric conversion modules. To meet these demands, resin materials are used as the base material of supports used in thermoelectric conversion modules (Patent Documents 1, 2, etc.). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2016 / 104615 [Patent Document 2] JP 2008-182160 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, resin substrates such as polyimide film and polyamide film used as a support for the thermoelectric conversion module of Patent Document 1, and insulating resin substrates such as polyimide-based resin and polysulfone-based resin used as a base layer for the flexible substrate constituting the flexible thermoelectric conversion element of Patent Document 2, have heat resistance and flexibility, but have low thermal conductivity in terms of the material properties derived from the resin. For example, even if the thickness is reduced to the mechanical strength limit of the thermoelectric conversion module, the thermal resistance cannot be sufficiently suppressed, which is an obstacle to further improvement in thermoelectric performance.
[0005] In view of the above, an object of the present invention is to provide a thermoelectric conversion module with further improved thermoelectric performance. [Means for solving the problem]
[0006] As a result of extensive research aimed at solving the above problems, the inventors discovered a thermoelectric conversion module with improved thermoelectric performance by using a base material (hereinafter sometimes referred to as a "substrate") having a specific thermal resistance as a support for the thermoelectric conversion elements that constitute the thermoelectric conversion module, and completed the present invention. That is, the present invention provides the following (1) to (10). (1) A thermoelectric conversion module including a substrate and a thermoelectric element layer made of a thermoelectric semiconductor composition, the thermoelectric semiconductor composition including a thermoelectric semiconductor material, a heat-resistant resin A, and an ionic liquid and / or an inorganic ionic compound, and the thermal resistance of the substrate is 0.35 K / W or less. (2) The thermoelectric conversion module according to (1) above, wherein the base material is made of an insulator. (3) The thermoelectric conversion module according to (1) or (2) above, wherein the base material has flexibility. (4) The thermoelectric conversion module according to any one of (1) to (3) above, wherein the thermal conductivity of the base material is 0.5 W / m·K or more. (5) The thermoelectric conversion module according to any one of (1) to (4) above, wherein the substrate has a thickness of 5 to 150 μm. (6) The thermoelectric conversion module according to any one of (1) to (5) above, wherein the base material contains a glass cloth and a heat-resistant resin B. (7) The thermoelectric conversion module according to (6) above, wherein the glass cloth is a woven glass cloth. (8) The thermoelectric conversion module according to (6) above, wherein the heat-resistant resin B is an epoxy resin or a polyimide resin. (9) The thermoelectric conversion module according to any one of (1) to (8) above, wherein the thermoelectric conversion module is composed of a π-type thermoelectric conversion element or an in-plane type thermoelectric conversion element. (10) The thermoelectric conversion module according to (9) above, wherein the configuration of the π-type thermoelectric conversion element or the in-plane type thermoelectric conversion element is used for cooling. Effect of the Invention
[0007] According to the present invention, it is possible to provide a thermoelectric conversion module with further improved thermoelectric performance. [Brief description of the drawings]
[0008] [Figure 1] FIG. 2 is a cross-sectional view illustrating an example of the configuration of a thermoelectric conversion module having a substrate used in the present invention. [Diagram 2] FIG. 4 is a cross-sectional view illustrating another example of the configuration of a thermoelectric conversion module having a substrate used in the present invention. [Diagram 3] FIG. 2 is a cross-sectional configuration diagram for explaining a cooling characteristic evaluation unit of a thermoelectric conversion module produced in an example of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] [Thermoelectric conversion module] The thermoelectric conversion module of the present invention is a thermoelectric conversion module including a substrate and a thermoelectric element layer made of a thermoelectric semiconductor composition, wherein the thermoelectric semiconductor composition includes a thermoelectric semiconductor material, a heat-resistant resin A, and an ionic liquid and / or an inorganic ionic compound, and the thermal resistance of the substrate is 0.35 K / W or less. In the thermoelectric conversion module of the present invention, by setting the thermal resistance of the base material, for example as a support for the thermoelectric conversion elements that constitute the thermoelectric conversion module, to 0.35 K / W or less, a larger temperature difference can be generated between the two sides of the thermoelectric conversion module. In this specification, the thermal resistance of the substrate is the thermal resistance due to thermal conduction, and the thermal conductivity of the material is λ [thermal conductivity of the substrate] (W / m k), the length of the heat flow path of the heat conduction is L [thickness of the substrate] (m), and the cross-sectional area of the heat flow path of the heat conduction is Ac [area of the cross section obtained by intersecting perpendicularly to the thickness direction of the substrate] (m 2 ), the thermal resistance Rc is expressed as Rc = L / λAc (K / W). In this specification, the evaluation of the thermal resistance of the substrate is performed between substrates having the same heat flow path cross-sectional area Ac, so the thermal resistance is essentially determined to depend on the thermal conductivity and thickness of the substrate.
[0010] 1 is a cross-sectional view for explaining an example of the configuration of a thermoelectric conversion module having a substrate used in the present invention. The thermoelectric conversion module 1 is configured as a so-called π-type thermoelectric conversion element, and includes a first substrate 2a and an opposing second substrate 2b, a P-type thermoelectric element layer 4 and an N-type thermoelectric element layer 5 formed between the first substrate 2a and the opposing second substrate 2b, a first electrode 3a formed on the first substrate 2a, and a second electrode 3b formed on the opposing second substrate 2b. 2 is a cross-sectional view for explaining another example of the configuration of a thermoelectric conversion module having a base material used in the present invention. The thermoelectric conversion module 11 is configured as a so-called in-plane type thermoelectric conversion element, and includes a first base material 12a and an opposing second base material 12b, a P-type thermoelectric element layer 14 and an N-type thermoelectric element layer 15 formed between the first base material 12a and the opposing second base material 12b, and a first electrode 13 formed on the first base material 12a.
[0011] <Base material> The thermoelectric conversion module of the present invention includes a substrate. As described above, for example, when configured as a π-type thermoelectric conversion element, it is preferable to include a second substrate having a second electrode facing a first substrate having a first electrode. When configured as an in-plane type thermoelectric conversion element, the second substrate facing the first substrate having a first electrode may or may not include a substrate. Furthermore, the first substrate and the second substrate facing the first substrate may be the same or different, and a plurality of substrates may be used.
[0012] The thermal resistance of the substrate used in the present invention is 0.35 K / W or less. If the thermal resistance exceeds 0.35 K / W, the heat dissipation in the substrate decreases, leading to a decrease in thermoelectric performance. The thermal resistance is preferably 0.30 K / W or less, more preferably 0.20 K / W or less, and even more preferably 0.15 K / W or less. If the thermal resistance is within this range, the heat dissipation in the substrate increases, leading to an improvement in thermoelectric performance. The substrate is not particularly limited as long as it is capable of forming and supporting a thermoelectric element layer, electrodes, etc. on its surface, but it is usually preferable that both the front and back surfaces are flat. The shape may be appropriately selected depending on the application, and examples of the shape include a rectangular parallelepiped, an elliptical cylinder, or a cylindrical shape.
[0013] The thermal conductivity of the substrate used in the present invention is preferably 0.5 W / m K or more, more preferably 1.5 W / m K or more, still more preferably 2.5 to 30.0 W / m K, and particularly preferably 3.0 to 20.0 W / m K. If the thermal conductivity is within this range, it becomes easier to adjust the thermal resistance value to the range specified in the present invention, and this leads to improved thermoelectric performance.
[0014] The substrate used in the present invention is preferably made of an insulator. By using an insulator as the substrate, electrical effects on the thermoelectric element layer, electrodes, etc. can be suppressed, and deterioration of thermoelectric performance can be prevented. In this specification, an insulator is an insulating material having a volume resistivity of 10 8 This refers to those with a resistance of Ω·m or more.
[0015] The thickness of the substrate is preferably 5 to 150 μm, more preferably 8 to 120 μm, still more preferably 10 to 100 μm, and particularly preferably 10 to 70 μm. When the thickness of the substrate is within this range, the substrate can obtain sufficient mechanical strength as a support for the thermoelectric element layer, etc., and can suppress deterioration of thermoelectric performance, leading to improved thermoelectric performance.
[0016] The substrate used in the present invention preferably contains glass cloth and heat-resistant resin B from the viewpoint of obtaining flexibility and heat resistance.
[0017] Examples of the glass fabric include glass woven fabric (glass cloth), glass nonwoven fabric, etc. The glass woven fabric and the nonwoven fabric may be used in combination. Among these, glass woven fabric is more preferable from the viewpoint of improving thermal conductivity.
[0018] Glass woven fabric is an aggregate of glass fibers, and is made by weaving yarns of bundled glass fibers. Examples of weaving methods include plain weave, sash weave, satin weave, twill weave, etc. Among these, plain weave is preferred from the viewpoint of thermal conductivity. Examples of glass materials constituting the glass woven fabric include E glass, C glass, A glass, S glass, T glass, D glass, NE glass, quartz, low dielectric constant glass, high dielectric constant glass, etc. Among these, E glass is preferred from the viewpoints of thermal conductivity and electrical insulation.
[0019] The heat-resistant resin B is not particularly limited, and examples thereof include epoxy resins, polyamideimide resins, polyimide resins, etc., which have crystallinity or liquid crystallinity. Among these, epoxy resins and polyimide resins are preferred from the viewpoint of heat resistance and versatility. More preferred is epoxy resin. The epoxy resin is not limited, and examples thereof include bisphenol type, novolac type, dicyclopentadiene type, biphenyl type, and tetrafunctional type.
[0020] The substrate may further contain an inorganic filler. From the viewpoint of mechanical strength, control of thermal conductivity, etc., examples of the inorganic filler include oxides such as titanium dioxide, aluminum hydroxide, aluminum oxide, magnesium oxide, and silica, hydroxides such as magnesium hydroxide, nitrides such as boron nitride, aluminum nitride, and silicon nitride, and carbides such as silicon carbide and boron carbide, and can be used as appropriate.
[0021] An example of a commercially available substrate that satisfies the thermal resistance requirement of this invention is a high thermal conductivity substrate with copper foil attached (manufactured by Risho Kogyo Co., Ltd., product name: CS-3295). The high thermal conductivity substrate itself is made of woven glass fabric and epoxy resin, and has a high thermal conductivity of 3.0 W / m K.
[0022] The method for producing the substrate is not particularly limited, but for example, the substrate can be produced by impregnating the glass woven fabric with a highly thermally conductive resin such as the epoxy resin, pre-drying the prepreg, cutting the prepreg to a predetermined size, stacking a predetermined number of sheets, placing copper foil on the outside in the case of a copper-clad laminate, and molding and integrating the sheets under heat and pressure under predetermined conditions.
[0023] The substrate preferably has a 5% weight loss temperature of 250°C or higher, more preferably 400°C or higher, as measured by thermogravimetric analysis. The thermal dimensional change rate measured at 200°C in accordance with JIS K7133 (1999) is preferably 0.5% or less, more preferably 0.3% or less. The linear expansion coefficient in the planar direction measured in accordance with JIS K7197 (2012) is 0.1 ppm·°C or less. -1 ~50ppm·℃ -1 and 0.1 ppm·℃ -1 ~30ppm·℃ -1 It is more preferable that:
[0024] <Thermoelectric element layer> The thermoelectric element layer used in the present invention comprises a thermoelectric semiconductor material, a heat-resistant resin A, and a thermoelectric semiconductor composition containing an ionic liquid and / or an inorganic ionic compound.
[0025] (Thermoelectric semiconductor materials) The thermoelectric semiconductor material used in the thermoelectric element layer is preferably pulverized to a predetermined size using, for example, a fine grinding device and used as thermoelectric semiconductor particles (hereinafter, the thermoelectric semiconductor material may be referred to as "thermoelectric semiconductor particles").
[0026] In the thermoelectric element layer used in the present invention, the thermoelectric semiconductor material constituting the P-type thermoelectric element layer and the N-type thermoelectric element layer is not particularly limited as long as it is a material that can generate a thermoelectromotive force by applying a temperature difference, and examples thereof include bismuth-tellurium-based thermoelectric semiconductor materials such as P-type bismuth telluride and N-type bismuth telluride; telluride-based thermoelectric semiconductor materials such as GeTe and PbTe; antimony-tellurium-based thermoelectric semiconductor materials; ZnSb, Zn 3 Sb 2、 Zinc 4 Sb 3 Zinc-antimony based thermoelectric semiconductor materials such as SiGe; Silicon-germanium based thermoelectric semiconductor materials such as Bi 2 Se 3 Bismuth selenide-based thermoelectric semiconductor materials such as β-FeSi 2 , CrSi 2 , MnSi 1.73 , Mg 2 Silicide-based thermoelectric semiconductor materials such as Si; oxide-based thermoelectric semiconductor materials; Heusler materials such as FeVAl, FeVAlSi, and FeVTiAl; TiS 2 Sulfide-based thermoelectric semiconductor materials such as the above are used.
[0027] Among these, the thermoelectric semiconductor material used in the present invention is preferably a bismuth-tellurium based thermoelectric semiconductor material such as P-type bismuth telluride or N-type bismuth telluride. The p-type bismuth telluride has a positive Seebeck coefficient and a positive carrier. For example, Bi X Te 3 Sb 2-XThose represented by are preferably used. In this case, X is preferably 0 < X ≤ 0.8, more preferably 0.4 ≤ X ≤ 0.6. When X is greater than 0 and less than or equal to 0.8, the Seebeck coefficient and the electrical conductivity increase, and the characteristics as a P-type thermoelectric conversion material are maintained, which is preferable. Further, in the N-type bismuth telluride, the carrier is an electron and the Seebeck coefficient is a negative value. For example, Bi 2 Te 3-Y Se Y Those represented by are preferably used. In this case, Y is preferably 0 ≤ Y ≤ 3 (when Y = 0: Bi 2 Te 3 ), more preferably 0.1 < Y ≤ 2.7. When Y is 0 or more and 3 or less, the Seebeck coefficient and the electrical conductivity increase, and the characteristics as an N-type thermoelectric conversion material are maintained, which is preferable.
[0028] The blending amount of the thermoelectric semiconductor particles in the thermoelectric semiconductor composition is preferably 30 to 99% by mass. More preferably, it is 50 to 96% by mass, and still more preferably, it is 70 to 95% by mass. If the blending amount of the thermoelectric semiconductor particles is within the above range, the Seebeck coefficient (the absolute value of the Peltier coefficient) is large, the decrease in electrical conductivity is suppressed, and only the thermal conductivity decreases, so that high thermoelectric performance is exhibited, and a film having sufficient film strength and flexibility can be obtained, which is preferable.
[0029] The average particle size of the thermoelectric semiconductor particles is preferably 10 nm to 200 μm, more preferably 10 nm to 30 μm, still more preferably 50 nm to 10 μm, and particularly preferably 1 to 6 μm. If it is within the above range, uniform dispersion becomes easy and the electrical conductivity can be increased. The method for obtaining thermoelectric semiconductor particles by pulverizing the thermoelectric semiconductor material is not particularly limited, and it may be pulverized to a predetermined size by a known fine pulverization device such as a jet mill, a ball mill, a bead mill, a colloid mill, a conical mill, a disk mill, an edge mill, a powder mill, a hammer mill, a pellet mill, a Willy mill, a roller mill, etc. The average particle size of the thermoelectric semiconductor particles was obtained by measurement using a laser diffraction particle size analyzer (Malvern, Mastersizer 3000) and was taken as the median value of the particle size distribution.
[0030] In addition, the thermoelectric semiconductor particles are preferably annealed (hereinafter, sometimes referred to as "annealing treatment A"). By carrying out the annealing treatment A, the crystallinity of the thermoelectric semiconductor particles is improved, and further, the surface oxide film of the thermoelectric semiconductor particles is removed, so that the Seebeck coefficient (absolute value of the Peltier coefficient) of the thermoelectric conversion material increases, and the thermoelectric figure of merit can be further improved. The annealing treatment A is not particularly limited, but is preferably carried out under an inert gas atmosphere such as nitrogen or argon, a reducing gas atmosphere such as hydrogen, or under vacuum conditions with a controlled gas flow rate, before preparing the thermoelectric semiconductor composition, so as not to adversely affect the thermoelectric semiconductor particles, and more preferably under a mixed gas atmosphere of an inert gas and a reducing gas. The specific temperature conditions depend on the thermoelectric semiconductor particles used, but it is usually preferable to carry out the annealing treatment at a temperature below the melting point of the particles and at 100 to 1500°C for several minutes to several tens of hours.
[0031] (Heat-resistant resin A) The heat-resistant resin A used in the present invention acts as a binder between thermoelectric semiconductor particles to enhance the flexibility of the thermoelectric element layer. The heat-resistant resin A is not particularly limited, but a heat-resistant resin A that maintains various physical properties such as mechanical strength and thermal conductivity as a resin without being impaired when the thermoelectric semiconductor particles are crystal-grown by annealing a thin film made of a thermoelectric semiconductor composition or the like is used. Examples of the heat-resistant resin A include polyamide resin, polyamideimide resin, polyimide resin, polyetherimide resin, polybenzoxazole resin, polybenzimidazole resin, epoxy resin, and copolymers having the chemical structure of these resins. The heat-resistant resin A may be used alone or in combination of two or more. Among these, polyamide resin, polyamideimide resin, polyimide resin, and epoxy resin are preferred because they have higher heat resistance and do not adversely affect the crystal growth of thermoelectric semiconductor particles in the thin film, and polyamide resin, polyamideimide resin, and polyimide resin are more preferred because they have excellent flexibility. When a polyimide film is used as the support, polyimide resin is more preferred as the heat-resistant resin A from the viewpoint of adhesion to the polyimide film. In the present invention, polyimide resin collectively refers to polyimide and its precursor.
[0032] The heat-resistant resin A preferably has a decomposition temperature of 300° C. or higher. If the decomposition temperature is within the above range, the resin does not lose its function as a binder and the flexibility of the thermoelectric element layer can be maintained even when a thin film made of the thermoelectric semiconductor composition is annealed, as described below.
[0033] The heat-resistant resin A preferably has a mass loss rate of 10% or less, more preferably 5% or less, and even more preferably 1% or less at 300° C. as measured by thermogravimetry (TG). If the mass loss rate is within the above range, the thermoelectric element layer can maintain its flexibility without losing its function as a binder, even when a thin film made of the thermoelectric semiconductor composition is annealed, as described below.
[0034] The blending amount of the heat-resistant resin A in the thermoelectric semiconductor composition is preferably 0.1 to 40 mass%, more preferably 0.5 to 20 mass%, and further preferably 1 to 20 mass%. When the blending amount of the heat-resistant resin A is within the above range, a film having both high thermoelectric performance and high film strength can be obtained.
[0035] (Ionic Liquid) The ionic liquid that can be contained in the thermoelectric semiconductor composition is a molten salt formed by combining a cation and an anion, and refers to a salt that can exist in a liquid state in any temperature range of -50°C or more and less than 400°C. In other words, the ionic liquid is an ionic compound whose melting point is in the range of -50°C or more and less than 400°C. The melting point of the ionic liquid is preferably -25°C or more and 200°C or less, more preferably 0°C or more and 150°C or less. The ionic liquid has characteristics such as extremely low vapor pressure and non-volatility, excellent thermal stability and electrochemical stability, low viscosity, and high ionic conductivity, and therefore can effectively suppress the reduction in electrical conductivity between thermoelectric semiconductor materials as a conductive auxiliary. In addition, the ionic liquid exhibits high polarity based on an aprotic ionic structure and has excellent compatibility with the heat-resistant resin A, so that the electrical conductivity of the thermoelectric conversion material can be made uniform.
[0036] The ionic liquid may be a known or commercially available one. For example, a mixture of a cationic component such as a pyridinium, pyrimidinium, pyrazolium, pyrrolidinium, piperidinium, imidazolium, etc., and a derivative thereof; a tetraalkylammonium-based amine-based cation and a derivative thereof; a phosphine-based cation such as a phosphonium, trialkylsulfonium, tetraalkylphosphonium, etc., and a derivative thereof; a lithium cation and a derivative thereof; and a mixture of a Cl cation and ... - , Br - , I - , AlCl 4 - , Al 2 Cl 7 - , B.F. 4 - , P.F. 6 - , ClO 4 - , NO 3 - , C.H. 3 COO - , C.F. 3 COO - , C.H. 3 SO 3 - , C.F.3 SO 3 - , (FSO 2 ) 2 N - , (CF 3 SO 2 ) 2 N - , (CF 3 SO 2 ) 3 C - , AsF 6 - , SbF 6 - , NbF 6 - , TaF 6 - , F(HF) n - , (CN) 2 N - , C 4 F 9 SO 3 - , (C 2 F 5 SO 2 ) 2 N - , C 3 F 7 COO - , (CF 3 SO 2 )(CF 3 CO)N - and an anion component such as the above.
[0037] Of the above ionic liquids, from the viewpoints of high-temperature stability, compatibility with thermoelectric semiconductor materials and resins, suppression of a decrease in the electrical conductivity in the gaps between thermoelectric semiconductor materials, and the like, it is preferable that the cationic component of the ionic liquid contains at least one selected from pyridinium cations and derivatives thereof, and imidazolium cations and derivatives thereof.
[0038] Specific examples of ionic liquids in which the cationic component contains a pyridinium cation and its derivatives include 4-methyl-butylpyridinium chloride, 3-methyl-butylpyridinium chloride, 4-methyl-hexylpyridinium chloride, 3-methyl-hexylpyridinium chloride, 4-methyl-octylpyridinium chloride, 3-methyl-octylpyridinium chloride, 3,4-dimethyl-butylpyridinium chloride, 3,5-dimethyl-butylpyridinium chloride, 4-methyl-butylpyridinium tetrafluoroborate, 4-methyl-butylpyridinium hexafluorophosphate, 1-butylpyridinium bromide, 1-butyl-4-methylpyridinium bromide, 1-butyl-4-methylpyridinium hexafluorophosphate, etc. Among these, 1-butyl-4-methylpyridinium bromide, 1-butylpyridinium bromide, and 1-butyl-4-methylpyridinium hexafluorophosphate are preferred.
[0039] Specific examples of ionic liquids in which the cationic component contains an imidazolium cation and a derivative thereof include [1-butyl-3-(2-hydroxyethyl)imidazolium bromide], [1-butyl-3-(2-hydroxyethyl)imidazolium tetrafluoroborate], 1-ethyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium bromide, 1-butyl-3-methylimidazolium chloride, 1-hexyl-3-methylimidazolium chloride, 1-octyl-3-methylimidazolium chloride, 1-decyl-3-methylimidazolium chloride, and 1-decyl-3-methylimidazolium chloride. Examples of the imidazolium bromide include 1-dodecyl-3-methylimidazolium chloride, 1-tetradecyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-hexyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium hexafluorophosphate, 1-butyl-3-methylimidazolium hexafluorophosphate, 1-methyl-3-butylimidazolium methyl sulfate, and 1,3-dibutylimidazolium methyl sulfate. Among these, [1-butyl-3-(2-hydroxyethyl)imidazolium bromide] and [1-butyl-3-(2-hydroxyethyl)imidazolium tetrafluoroborate] are preferred.
[0040] The above ionic liquid has an electrical conductivity of 10 -7 If the ionic conductivity is in the above range, the conductive additive can effectively suppress the decrease in electrical conductivity between thermoelectric semiconductor materials.
[0041] The ionic liquid preferably has a decomposition temperature of 300° C. or higher. If the decomposition temperature is within the above range, the effect as a conductive auxiliary agent can be maintained even when a thin film made of the thermoelectric semiconductor composition is annealed, as described below.
[0042] The ionic liquid preferably has a mass loss rate of 10% or less, more preferably 5% or less, and even more preferably 1% or less at 300° C. as measured by thermogravimetry (TG). If the mass loss rate is within the above range, the ionic liquid can maintain its effect as a conductive auxiliary even when a thin film made of the thermoelectric semiconductor composition is annealed, as described below.
[0043] The amount of the ionic liquid in the thermoelectric semiconductor composition is preferably 0.01 to 50 mass%, more preferably 0.5 to 30 mass%, and even more preferably 1.0 to 20 mass%. When the amount of the ionic liquid is within the above range, the decrease in electrical conductivity is effectively suppressed, and a film having high thermoelectric performance is obtained.
[0044] (Inorganic ionic compounds) The inorganic ionic compound used in the present invention is a compound composed of at least a cation and an anion. The inorganic ionic compound is a solid at room temperature, has a melting point at any temperature in the temperature range of 400 to 900°C, and has characteristics such as high ionic conductivity, so that it can suppress the decrease in electrical conductivity between thermoelectric semiconductor particles as a conductive auxiliary.
[0045] The amount of the inorganic ionic compound in the thermoelectric semiconductor composition is preferably 0.01 to 50 mass%, more preferably 0.5 to 30 mass%, and further preferably 1.0 to 10 mass%. When the amount of the inorganic ionic compound is within the above range, the decrease in electrical conductivity can be effectively suppressed, and as a result, a film with improved thermoelectric performance can be obtained. In addition, when an inorganic ionic compound and an ionic liquid are used in combination, the total content of the inorganic ionic compound and the ionic liquid in the thermoelectric semiconductor composition is preferably 0.01 to 50 mass%, more preferably 0.5 to 30 mass%, and even more preferably 1.0 to 10 mass%.
[0046] The thickness of the thermoelectric element layer is not particularly limited, but from the standpoint of thermoelectric performance and film strength, it is preferably 100 nm to 1000 μm, more preferably 300 nm to 600 μm, and even more preferably 5 to 400 μm.
[0047] The P-type thermoelectric element layer and the N-type thermoelectric element layer as thin films made of the thermoelectric semiconductor composition are preferably further annealed (hereinafter, sometimes referred to as "annealing treatment B"). By carrying out the annealing treatment B, the thermoelectric performance can be stabilized and the thermoelectric semiconductor particles in the thin film can be crystallized, thereby further improving the thermoelectric performance. The annealing treatment B is not particularly limited, but is usually carried out under an inert gas atmosphere such as nitrogen or argon, under a reducing gas atmosphere, or under vacuum conditions with a controlled gas flow rate, and is carried out at 100 to 500°C for several minutes to several tens of hours, depending on the heat resistance temperature of the resin and ionic compound used.
[0048] <Electrode> The thermoelectric conversion module of the present invention preferably includes a first electrode. When configured as a π-type thermoelectric conversion element, it is preferable that a second electrode is further included on a second substrate facing a first substrate having the first electrode. The first electrode and the second electrode on the second substrate facing the first substrate may be the same or different. When configured as an in-plane type thermoelectric conversion element, the second electrode may or may not be present as long as there is a first electrode. The metal materials used for the first electrode and the second electrode are not particularly limited, but are preferably copper, gold, nickel, aluminum, rhodium, platinum, chromium, palladium, stainless steel, molybdenum, or an alloy containing any of these metals, and may be formed as a single layer or a multilayer structure by combining a plurality of layers. The thickness of the first electrode layer and the second electrode layer is preferably 10 nm to 200 μm, more preferably 30 nm to 150 μm, and further preferably 50 nm to 120 μm. If the thickness of the first electrode layer and the second electrode layer is within the above range, the electrical conductivity is high and the resistance is low, and sufficient strength as an electrode is obtained.
[0049] The first electrode and the second electrode are formed using the above-mentioned metal material. The method of forming the first electrode and the second electrode includes a method of forming an electrode without a pattern on a substrate, and then processing the electrode into a predetermined pattern shape by a known physical or chemical treatment mainly based on a photolithography method, or a combination of these, or a method of directly forming an electrode pattern by a screen printing method, an inkjet method, or the like. Methods for forming an electrode without a pattern include dry processes such as PVD (physical vapor deposition) methods such as vacuum deposition, sputtering, and ion plating, or CVD (chemical vapor deposition) methods such as thermal CVD and atomic layer deposition (ALD), or wet processes such as various coating methods and electrodeposition methods such as dip coating, spin coating, spray coating, gravure coating, die coating, and doctor blade methods, silver halide plating, electrolytic plating, electroless plating, and lamination of metal foils, and are appropriately selected depending on the material of the electrode. From the viewpoint of thermoelectric performance, high electrical conductivity and high thermal conductivity are required, so it is preferable to use electrodes formed by plating or vacuum film formation. Vacuum film formation methods such as vacuum deposition and sputtering, as well as electrolytic plating and electroless plating are preferable because they can easily achieve high electrical conductivity and high thermal conductivity. Depending on the size and dimensional accuracy of the formed pattern, a hard mask such as a metal mask can be used to easily form a pattern.
[0050] The thermoelectric conversion module of the present invention is not particularly limited, but is preferably composed of a π-type thermoelectric conversion element or an in-plane type thermoelectric conversion element. In one embodiment, the thermoelectric conversion module is preferably used for cooling purposes in the configuration of a π-type thermoelectric conversion element or an in-plane type thermoelectric conversion element. In another embodiment, the thermoelectric conversion module is preferably used for power generation purposes in the configuration of a π-type thermoelectric conversion element or an in-plane type thermoelectric conversion element.
[0051] (Method of manufacturing thermoelectric conversion module) The thermoelectric conversion module of the present invention can be manufactured by a method including a step of forming electrodes on a substrate (hereinafter sometimes referred to as an "electrode formation step"), a step of applying and drying the thermoelectric semiconductor composition to form a thermoelectric element layer (hereinafter sometimes referred to as a "thermoelectric element layer formation step"), a step of annealing the thermoelectric element layer (hereinafter sometimes referred to as an "annealing step"), and a step of bonding the annealed substrate to another substrate (hereinafter sometimes referred to as a "bonding step"). Hereinafter, the steps included in the method for producing a thermoelectric conversion module of the present invention will be described in order.
[0052] (Electrode formation process) The electrode formation step is, for example, a step of forming a pattern made of the above-mentioned metal material on a first base material, and the method of forming the electrode on the base material and the method of forming the pattern are as described above. In particular, when manufacturing the above-mentioned π-type thermoelectric conversion module or the like, the electrode formation step includes a step of forming a pattern made of the above-mentioned metal material on a second base material facing the first base material.
[0053] (Thermoelectric element layer formation process) The thermoelectric element layer forming step is, for example, a step of applying the thermoelectric semiconductor composition onto an electrode. Methods for applying the thermoelectric semiconductor composition onto an electrode on a first substrate include known methods such as screen printing, flexographic printing, gravure printing, spin coating, dip coating, die coating, spray coating, bar coating, doctor blade, etc., and are not particularly limited. When forming a coating film in a pattern, a screen printing method, a slot die coating method, etc., which can easily form a pattern using a screen plate having a desired pattern, are preferably used. The coating film thus obtained is then dried to form a thermoelectric element layer, and the drying method may be a conventionally known drying method such as hot air drying, hot roll drying, infrared irradiation, etc. The heating temperature is usually 80 to 150° C., and the heating time varies depending on the heating method, but is usually several seconds to several tens of minutes. When a solvent is used in the preparation of the thermoelectric semiconductor composition, the heating temperature is not particularly limited as long as it is within a temperature range in which the solvent used can be dried. The same applies to the case where the thermoelectric semiconductor composition is applied onto an electrode on a second substrate.
[0054] Another example of the thermoelectric element layer forming step is a method in which the thermoelectric element layer is previously produced as chips of a thermoelectric conversion material, and a plurality of the obtained chips are placed on predetermined electrodes on a substrate and bonded. As a method for producing a chip of a thermoelectric conversion material, for example, a chip of a thermoelectric conversion material made of a thermoelectric semiconductor composition can be produced by the following method. First, a sacrificial layer is formed on a substrate such as glass, alumina, silicon, etc., and a thermoelectric element layer (hereinafter, sometimes referred to as a "chip of thermoelectric conversion material") is formed on the obtained sacrificial layer by the method described above. Next, the obtained chip of thermoelectric conversion material is annealed (according to the conditions of annealing treatment B), and the chip of thermoelectric conversion material is peeled off from the sacrificial layer on the substrate, thereby manufacturing the chip of thermoelectric conversion material as an individual piece. The sacrificial layer is made of a resin such as polymethylmethacrylate or polystyrene, or a release agent such as a fluorine-based release agent or a silicone-based release agent.
[0055] (Annealing process) The annealing step is, for example, a step of annealing the thermoelectric element layer in a form having the first base material, the electrode, and the thermoelectric element layer obtained above in this order. The annealing step is performed in the annealing step B described above.
[0056] (Laminating process) The bonding process is, for example, a process of bonding a first substrate having an electrode and a thermoelectric element layer obtained in the annealing process to an opposing second substrate or a second substrate having a second electrode, to produce a thermoelectric conversion module. In the case of a second substrate having a second electrode, the laminating agent used for the lamination may be a conductive paste, etc. Examples of the conductive paste include copper paste, silver paste, nickel paste, etc., and in the case of using a binder, examples of the conductive paste include epoxy resin, acrylic resin, urethane resin, etc. In addition, in the case of the second substrate not having a second electrode, a resin material can be used. The resin material preferably contains a polyolefin resin, an epoxy resin, or an acrylic resin. Furthermore, the resin material preferably has adhesiveness, low water vapor permeability, and insulating properties. In this specification, having adhesiveness means that the resin material has adhesiveness, adhesion, and pressure-sensitive adhesiveness that can be bonded by pressure at the initial stage of attachment. Methods for applying the laminating agent onto the substrate include known methods such as screen printing and dispensing.
[0057] When a solder material layer is used for bonding to the electrodes in the bonding step, a solder-receiving layer can be used to improve the bonding strength. For example, a method for forming a solder-receiving layer on a chip of a thermoelectric conversion material obtained by the above-mentioned manufacturing method is as follows. After forming a solder-receiving layer on all surfaces of the thermoelectric conversion material chip, which has an upper surface, a lower surface, and a side surface, the solder-receiving layer formed on the side surface of the thermoelectric conversion material chip is entirely removed or part of the resulting solder-receiving layer is removed to form the solder-receiving layer. The solder-receiving layer preferably contains a metal material. The metal material is preferably at least one selected from gold, silver, rhodium, platinum, chromium, palladium, tin, nickel, and an alloy containing any of these metal materials. Among these, a two-layer structure of gold, silver, nickel, tin and gold, or nickel and gold is more preferable, and silver is even more preferable from the viewpoints of material cost, high thermal conductivity, and bonding stability. The solder-receiving layer is required to have high electrical conductivity and high thermal conductivity in order to maintain thermoelectric performance, and from the viewpoint of reducing the contact resistance at the interface with the thermoelectric conversion material chip, it is preferable to use a solder-receiving layer formed by a plating method or a vacuum film formation method. The solder material constituting the solder material layer may be appropriately selected taking into consideration the heat resistance temperature of the heat-resistant resin A contained in the resin film and the chip of the thermoelectric conversion material, as well as electrical conductivity and thermal conductivity, and examples of known materials include Sn, Sn / Pb alloy, Sn / Ag alloy, Sn / Cu alloy, Sn / Sb alloy, Sn / In alloy, Sn / Zn alloy, Sn / In / Bi alloy, Sn / In / Bi / Zn alloy, Sn / Bi / Pb / Cd alloy, Sn / Bi / Pb alloy, Sn / Bi / Cd alloy, Bi / Pb alloy, Sn / Bi / Zn alloy, Sn / Bi alloy, Sn / Bi / Pb alloy, Sn / Pb / Cd alloy, and Sn / Cd alloy. From the viewpoints of lead-free and / or cadmium-free, melting point, electrical conductivity, and thermal conductivity, alloys such as 43Sn / 57Bi alloy, 42Sn / 58Bi alloy, 40Sn / 56Bi / 4Zn alloy, 48Sn / 52In alloy, and 39.8Sn / 52In / 7Bi / 1.2Zn alloy are preferred. Methods for applying the solder material onto the electrodes of the substrate include known methods such as screen printing and dispensing.
[0058] According to the method for producing a thermoelectric conversion module of the present invention, a thermoelectric conversion module having flexibility and improved thermoelectric performance can be easily obtained. EXAMPLES
[0059] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples in any way.
[0060] The substrates used in the examples and comparative examples and the thermoelectric performance of the produced thermoelectric conversion modules were evaluated by the following methods.
[0061] <Substrate evaluation> (a) Thermal conductivity and thermal resistance of the substrate The thermal conductivity of the substrate was measured at 23°C using a thermal conductivity measuring device (Advance Riko Co., Ltd., Steady-state thermal conductivity measuring device GH-1) according to ASTM E1530 by the disk heat flow meter method. The thermal conductivity λ (W / m K) of the substrate, as well as the thickness L (m) and cross-sectional area of the substrate (cross-sectional area of the heat flow path for heat conduction) Ac (m 2 ) the thermal resistance Rc [= L / λAc (K / W)] was calculated.
[0062] <Thermoelectric performance evaluation> (b) Electrical resistance evaluation of thermoelectric conversion module The electrical resistance (module resistance) between the extraction electrodes of the obtained thermoelectric conversion module was measured in an environment of 25° C.×50% RH using a low resistance measuring device (manufactured by HIOKI EE Corporation, model number: RM3545). (c) Evaluation of the cooling characteristics of a thermoelectric conversion module The cooling characteristics of the obtained thermoelectric conversion module were evaluated using a cooling characteristic evaluation unit. FIG. 3 is a cross-sectional configuration diagram for explaining a cooling characteristic evaluation unit of a thermoelectric conversion module used in the examples. The cooling characteristic evaluation unit 21 is composed of temperature measuring plates 23 and 24 with K-type thermocouples inserted on both sides of a thermoelectric conversion module 22, and temperature controllers 25 and 26, and is insulated by being placed under a vacuum (degree of vacuum: 0.1 Pa or less), and the temperatures of the heat absorption surface 27 and the heat dissipation surface 28 of the thermoelectric conversion module were adjusted to 85° C. by the temperature controllers 25 and 26. Thereafter, a current was applied to the thermoelectric conversion module 22, and the temperature difference between the heat absorption surface 27 and the heat dissipation surface 28 was measured. Note that the temperature on the heat absorption surface 27 side was controlled to be maintained at 85° C. by the temperature controller when the current was applied.
[0063] Example 1 (1) Preparation of thermoelectric semiconductor composition (Preparation of thermoelectric semiconductor particles) P-type bismuth telluride Bi, a bismuth-tellurium based thermoelectric semiconductor material 0.4 Te 3 Sb 1.6(manufactured by Kojundo Chemical Laboratory, particle size: 90 μm) was pulverized in a nitrogen gas atmosphere using a planetary ball mill (manufactured by Fritsch Japan, Premium line P-7) to produce thermoelectric semiconductor particles T1 with an average particle size of 2.0 μm. In addition, N-type bismuth telluride Bi, a bismuth-tellurium based thermoelectric semiconductor material, 2 Te 3 (manufactured by Kojundo Chemical Laboratory, particle size: 90 μm) was pulverized in the same manner as above to produce thermoelectric semiconductor particles T2 with an average particle size of 2.8 μm. The particle size distribution of the thermoelectric semiconductor particles T1 and T2 obtained by pulverization was measured using a laser diffraction particle size analyzer (Malvern, Mastersizer 3000). (Preparation of Coating Solution of Thermoelectric Semiconductor Composition) Coating liquid (P) The p-type bismuth telluride Bi obtained above 0.4 Te 3.0 Sb 1.6 A coating liquid (P) consisting of a thermoelectric semiconductor composition was prepared by mixing and dispersing 72.0 parts by mass of the particles T1, 15.5 parts by mass of polyamideimide (Comporacene AI301, manufactured by Arakawa Chemical Industries, Ltd., solvent: N-methylpyrrolidone, solid content: 19% by mass) as a heat-resistant resin A, and 12.5 parts by mass of N-butylpyridinium bromide as an ionic liquid. Coating fluid (N) The obtained N-type bismuth telluride Bi 2 Te 3 A coating liquid (N) consisting of a thermoelectric semiconductor composition was prepared by mixing and dispersing 78.9 parts by mass of the particles T2, 17.0 parts by mass of polyamideimide (Comporacene AI301, manufactured by Arakawa Chemical Industries, Ltd., solvent: N-methylpyrrolidone, solid content: 19% by mass) as a heat-resistant resin A, and 4.1 parts by mass of N-butylpyridinium bromide as an ionic liquid. (2) Formation of thin films of thermoelectric conversion materials A sacrificial layer was formed on a 0.7 mm thick glass substrate (product name: blue plate glass, manufactured by Kawamura Kuzo Shoten Co., Ltd.) by spin coating a polymethyl methacrylate resin solution with a solid content of 10 mass %, prepared by dissolving polymethyl methacrylate resin (PMMA) (product name: polymethyl methacrylate, manufactured by Sigma-Aldrich Co., Ltd.) in toluene, so that the thickness after drying was 3.0 μm. Next, the coating solution (P) prepared in (1) above was applied onto the sacrificial layer by screen printing using a metal mask, and dried in an argon atmosphere at a temperature of 125°C for 15 minutes to form a thin film with a thickness of 270 μm. Next, the obtained thin film was heated at a heating rate of 5 K / min in an atmosphere of a mixed gas of hydrogen and argon (hydrogen:argon = 3 volume %: 97 volume %) and held at 450°C for 1 hour to anneal the thin film, causing crystal growth of the particles of the thermoelectric semiconductor material, resulting in the formation of P-type bismuth telluride Bi 0.4 Te 3 Sb 1.6 A rectangular parallelepiped P-type thermoelectric conversion material chip having a top and bottom surface each measuring 1.65 mm×1.65 mm and a thickness of 200 μm was obtained. In addition, N-type bismuth telluride Bi was prepared in the same manner, except that the coating solution (N) prepared in (1) above was used and dried at 125°C for 7 minutes under an argon atmosphere. 2 Te 3 A rectangular parallelepiped N-type thermoelectric conversion material chip having a top and bottom surface each measuring 1.65 mm×1.65 mm and a thickness of 250 μm was obtained.
[0064] (3) Formation of solder-receiving layer After the annealing treatment, the P-type and N-type thermoelectric conversion material chips were peeled off from the glass substrate, and a solder-receptive layer [Ni (thickness: 2 μm) laminated with Au (thickness: 30 nm)] was provided on all surfaces of the P-type and N-type thermoelectric conversion material chips by electroless plating. Next, the solder-receiving layers on the side surfaces of the P-type and N-type thermoelectric conversion material chips were removed by mechanical polishing, i.e., using sandpaper (grit 2000), so that the chips had dimensions of 1.5 mm x 1.5 mm, thereby obtaining P-type and N-type thermoelectric conversion material chips having solder-receiving layers only on the top and bottom surfaces. Note that, in order to completely remove the solder-receiving layers, part of the side walls were also polished.
[0065] <Fabrication of thermoelectric conversion module> Using the obtained chips of P-type and N-type thermoelectric conversion materials having solder acceptance layers only on the top and bottom surfaces, a π-type thermoelectric conversion element consisting of 18 pairs each of P-type and N-type thermoelectric conversion material chips was fabricated as follows. First, a high thermal conductivity substrate with copper foil attached on both sides (manufactured by Risho Kogyo Co., Ltd., product name: CS-3295; 10 mm x 20 mm, thickness: 60 μm; copper foil, thickness: 35 μm) was prepared, and a nickel layer (thickness: 3 μm) and a gold layer (thickness: 40 nm) were laminated in this order on the copper foil of the high thermal conductivity substrate by electroless plating, and then an electrode pattern (1.5 x 3.2 mm, distance between adjacent electrodes: 0.2 mm, 6 columns x 3 rows) was formed only on one side to prepare a substrate with electrodes (lower electrode substrate). After that, a solder material layer was stencil printed on the electrode using solder paste 42Sn / 57Bi / Ag alloy (manufactured by Nippon Handa Co., Ltd., product name: PF141-LT7H0) as the solder material (thickness before heating: 50 μm). Next, one side of the solder-receiving layer of each of the P-type and N-type thermoelectric conversion material chips obtained above was placed on the solder material layer, heated at 180°C for 1 minute, and then cooled (thickness of the solder material layer after heating and cooling: 30 μm), thereby placing the P-type and N-type thermoelectric conversion material chips on the electrodes, respectively. Furthermore, the solder paste was printed as a solder material layer (thickness before heating: 50 μm) on the other side of the solder acceptance layer of each of the P-type and N-type thermoelectric conversion material chips, and the obtained solder material layer was bonded to the electrodes of an upper electrode substrate (an electrode substrate with electrodes patterned so that a π-type thermoelectric conversion module is obtained when bonded to the lower electrode substrate; the substrate, electrode material, thickness, etc. are the same as those of the lower electrode substrate) and heated at 190°C for 2 minutes to obtain a π-type thermoelectric conversion module consisting of 18 pairs each of the P-type and N-type thermoelectric conversion material chips. The obtained thermoelectric conversion module was evaluated for module resistance (electrical resistance) and temperature difference ΔT between the heat absorption surface and the heat radiation surface under the aforementioned evaluation conditions. The evaluation results, including thermal conductivity and thermal resistance, are shown in Table 1.
[0066] Comparative Example 1 A thermoelectric conversion module of Comparative Example 1 was produced in the same manner as in Example 1, except that the high thermal conductivity substrate in Example 1 was changed to a polyimide film substrate (manufactured by Toray DuPont, product name "Kapton"; 10 mm x 20 mm, thickness: 12.5 μm). The obtained thermoelectric conversion module was evaluated for module resistance (electrical resistance) and temperature difference ΔT between the heat absorption surface and the heat radiation surface under the above-mentioned evaluation conditions in the same manner as in Example 1. The evaluation results, including the thermal conductivity and thermal resistance, are shown in Table 1.
[0067] [Table 1]
[0068] The thermoelectric conversion module of Example 1, in which the substrate of the thermoelectric conversion module is a flexible, highly thermally conductive substrate, can obtain a larger temperature difference than the thermoelectric conversion module of Comparative Example 1, in which the substrate is a conventional substrate having a low thermal conductivity, a polyimide film, and therefore can obtain better cooling performance. [Industrial Applicability]
[0069] INDUSTRIAL APPLICABILITY The thermoelectric conversion module of the present invention has flexibility and excellent thermoelectric performance, and therefore can be used, for example, in applications for suppressing heat accumulation that occurs when electronic devices and the like are made smaller and thinner. Specifically, examples of this include cooling the CPUs (Central Processing Units) installed in smartphones, tablet PCs, etc., as well as temperature control of various sensors such as image sensors, such as CMOS (Complementary Metal Oxide Semiconductor Image Sensors) and CCD (Charge Coupled Devices), which are semiconductor elements. Furthermore, the present invention can be applied to power generation applications in which exhaust heat from various combustion furnaces such as factories, waste combustion furnaces, and cement combustion furnaces, exhaust heat from automobile combustion gases, and exhaust heat from electronic devices are converted into electricity. [Explanation of symbols]
[0070] 1: Thermoelectric conversion module 2a: First substrate 2b: Second substrate 3a: first electrode 3b: Second electrode 4: P-type thermoelectric element layer 5: N-type thermoelectric element layer 11: Thermoelectric conversion module 12a: First substrate 12b: Second substrate 13: First electrode 14: P-type thermoelectric element layer 15: N-type thermoelectric element layer 21: Cooling characteristic evaluation unit 22: Thermoelectric conversion module 23,24: Measuring plate 25,26:Temperature controller 27: Heat absorbing surface 28: Heat dissipation surface
Claims
1. A thermoelectric conversion module including a substrate and a thermoelectric element layer made of a thermoelectric semiconductor composition, the thermoelectric semiconductor composition including a thermoelectric semiconductor material, a heat-resistant resin A, and an ionic liquid and / or an inorganic ionic compound; The substrate is made of an insulator, The substrate is flexible, The thermal conductivity of the base material is 0.5 W / m K or more, The thickness of the substrate is 5 to 150 μm, The substrate comprises a glass cloth and a heat-resistant resin B, The thermal resistance of the substrate is 0.35 K / W or less.
2. The thermoelectric conversion module according to claim 1 , wherein the glass cloth is a woven glass cloth.
3. The thermoelectric conversion module according to claim 1 , wherein the heat-resistant resin B is an epoxy resin, a polyamide-imide resin, or a polyimide resin.
4. The thermoelectric conversion module according to any one of claims 1 to 3, wherein the thermoelectric conversion module is composed of a π-type thermoelectric conversion element or an in-plane type thermoelectric conversion element.
5. The thermoelectric conversion module according to claim 4 , wherein a configuration of the π-type thermoelectric conversion element or the in-plane type thermoelectric conversion element is used for cooling.
Citation Information
Patent Citations
Thermoelectric power-generating element module comprising electric insulating film
JP2001326394A
Thermoelectric conversion device
JP2003174203A
Flexible thermoelectric conversion element and its manufacturing method
JP2008182160A
Thermoelectric element module
JP2009141079A
Insulating / heat dissipating substrate for power module
JP2012227271A